ANALYSIS OF THE APPLICATION SHOW AND TELL METHOD TO IMPROVE SPEAKING SKILLS OF STUDENTS OF CLASS 2 SDN CANGGU 1 - Binti Umi Malikah; Betty Oktavia Rahmayanti; Muhamad Mujib; Conny Dian Sumadi (Citra Dharma Cindekia, 2022)
Speaking skill is an important skill to be learned by someone related to their nature as a social being. One of the learning methods that can be applied in learning speaking skills is the show and tell method. The purpose of this study was to analyze the improvement of the speaking skills of grade 2 students through the application of the show and tell learning method. The population used in this study were all 2nd grade students of SD Negeri 1 Canggu in the 2021/2022 academic year. While the samples in this study were some of the 2nd grade students of SD Negeri Canggu 1 for the academic year 2021/2022. Data collection techniques used are interviews, observation, documentation, and literature study. Data analysis techniques used in this research are reduction, data presentation, and conclusion drawing. The results of the analysis show that there is a significant increase in students' speaking skills when teaching and learning activities use the show and tell learning method. This research can be used as input for educators to choose innovative learning methods to improve students' speaking skills.